Organizational change: An action-oriented toolkit - Deszca, Gene; Ingols, Cynthia; Atanassova, Evelina; Cawsey, Tupper F. (New Delhi Sage India, 2025)
The world has continued to churn in very challenging ways since the publishing of the fourth edition of this text. Increasing international tensions, wars in the Ukraine, Sudan, and elsewhere, uneven and shifting global patterns of growth in the aftermath of COVID shutdowns, inflationary pressures, rising interest rates, political instability, and increasing income inequality are heightening political instability in many parts of the world. Serious trade disputes are threatening to transform trade patterns and reshaping supply chains.